Squamous papillomatosis of the trachea and bronchi - Le Roux, B. T. (1969)
A squamous papilloma which occluded the trachea of a young man was managed by resection at tracheotomy. Thereafter it was possible further to examine the bronchi bronchoscopically, and widespread papillomatosis confined to the left bronchi was seen. Following bronchography, which showed left-sided bronchiectasis, left pneumonectomy was undertaken. Case details are presented and the literature which relates to bronchial papillomatosis is reviewed.